Magnesium-containing mixed coatings on zirconia for dental implants: mechanical characterization and in vitro behavior. (July 2015) - Pardun, Karoline; Treccani, Laura; Volkmann, Eike; Streckbein, Philipp; Heiss, Christian; Gerlach, Juergen W; Maendl, Stephan; Rezwan, Kurosch
An important challenge in the field of dental and orthopedic implantology is the preparation of implant coatings with bioactive functions that feature a high mechanical stability and at the same time mimic structural and compositional properties of native bone for a better bone ingrowth. This study investigates the influence of magnesium addition to zirconia-calcium phosphate coatings. The mixed coatings were prepared with varying additions of either magnesium oxide or magnesium fluoride to yttria-stabilized zirconia and hydroxyapatite. The coatings were deposited on zirconia discs and screw implants by wet powder spraying. Microstructure studies confirm a porous coating with similar roughness and firm adhesion not hampered by the coating composition. The coating morphology, mechanical flexural strength and calcium dissolution showed a magnesium content-dependent effect. Moreover, the in vitro results obtained with human osteoblasts reveal an improved biological performance caused by the presence of Mg 2+ ions. The magnesium-containing coatings exhibited better cell proliferation and differentiation in comparison to pure zirconia-calcium phosphate coatings. In conclusion, these results demonstrate that magnesium addition increases the bioactivity potential of zirconia-calcium phosphate coatings and is thus a highly suitable candidate for bone implant coatings.